PENINGKATAN PENGETAHUAN IBU DAN KADER DALAM RANGKA PENURUNAN ANGKA STUNTING MEWUJUDKAN INDONESIA SEHAT DI PADUKUHAN PONGGOK - Mustofa, Moh Makfi; Syalim, Aizan; Ardiansyah, Evan; Khoiriyah, Niswatun; Salsabila, Nayla Rahma; Annisa, Nanda; Febriyani; Rohmah, Fatimatur; Susilawati, Sepfitri Eka; Saputri, Sindy; Nurinda, Eva (Universitas 'Aisyiyah Surakarta, 2025)
In the modern era, stunting is still one of the issues that need attention in the health sector in Indonesia. The stunting rate in Indonesia from 2022 to 2023 is still at the same figure, which is around 21%. From SKI data, it is also known that the prevalence of stunting in the DIY region increased from 2022, namely 16.4% to 18% in 2023. In the process of child growth and development, mothers have a fairly important role. The aim of this activity is to increase public awareness, especially pregnant women and mothers of toddlers, about the importance of preventing stunting to improve the health quality of future generations. Through counseling and demonstrations, the public is given an understanding of cheap, nutritious, and easily available local foods, and several supplements that are good for fulfilling the micronutrients of pregnant women. Evaluation through questionnaires showed an increase in participant understanding, where the understanding score increased from 82.36 to 90.28. This shows that this activity is effective in increasing public knowledge and health cadres in Dukuh Ponggok, Sidomulyo Village, Bambanglipuro District. This counseling is expected to have a positive impact in reducing stunting rates through increasing awareness and implementing healthy eating patterns in families